N-Methyl-N-Propylpyrrolidinium Tetrafluoroborate : new solvent for heck reaction - Mohamad Hafiz Ahmad Tajudin; Mustaffa Shamsuddin; Sofian Ibrahim; Hasnah Mohd. Sirat; Zakaria Bahari; Simposium Kimia Analisis Kebangsaan (ke-16 : 2003 : Kuching, Sarawak) (Skudai : Universiti Teknologi Malaysia, 2003)
42